Willingness to Use Overhead Bridge Facilities Based on Theory of Planned Behavior - Sundararajan, Komala Devi (International Journal of Integrated Engineering, 2020)
Overhead Bridge is the most vital crossing facilities for pedestrian to cross the busy road. This bridge is most important to implement the way to prevent the incident and to create awareness for the pedestrian to take a safety crossing behavior in order to avoid the accident crashes. The objective of this study is to estimate the frequency of overhead bridge usage and the relationship between characteristics and attitude among pedestrian. In understanding this output, Theory of Planned Behavior turned into used in the study to decide whether the characteristics and attitude affect the behavior of pedestrian that concerning the accident. This study was conducted at overhead bridges which located between Ayer Hitam to Batu Pahat. The sample for this study consists of 200 respondents. Set questionnaires which contain 30 items of questions were used to collect the data. The data were analysis using descriptive analysis, correlation analysis and regression analysis. Data was analyzed using SPSS. There were 86 males and 114 females are evaluated the questionnaires. There were 157 respondents are who below 30 years and younger people. Correlation for all the factors of TPB are shows positive linear relationship. Attitude and Perceived Behavior Control show a significant to predict intention. Intention also showed strong relationship to the behavior. Lastly, Perceived Behavior Control showed strong relationship to the behavior. Attitude and Perceived Behavior Control may be having an impact on pedestrian to willing used overhead bridge and prevent pedestrians’ accidents and fatalities.